Tafsir dan Politik Kekuasaan di Indonesia - Taryudi Taryudi; Tatan Setiawan (Jurnal Iman dan Spiritualitas, 2021)
This paper seeks to investigate the developmental style of interpretive thought in Indonesia amid the dynamics of the political power that surrounds it. Most of the interpretations that are products of thought can be categorized into the scope of knowledge, while power politics as a dynamic cannot be separated from power. A conception is needed to form a relationship between interpretation and power politics in Indonesia. Foucault's theory of the relationship between power and knowledge can be used as an alternative to bridge these needs. The method used in this paper is descriptive analysis based on library research. The findings of this study are that the development pattern of interpretive thought in Indonesia amid the political power surrounding it shows that the developing thinking is influenced by the Adab Ijtimā'i (social ethics) style. Through Foucault's theory, it appears that there is a relationship between power which in this context is represented in the period of power politics in the three eras of power in Indonesia during the independence era, namely: the Old Order era, the New Order era, and the Reform era and the knowledge represented in the products of the interpretations of the mufasirnya adapted to the era of political power.